FID NMR Studies of Suspensions and Porous Media - Kishenkov, Oleg; Menshikov, Leonid; Maximychev, Alexander (Diffusion Fundamentals, 2017)
Nuclear Magnetic Resonance is used for the determination of the properties of porous media in Geophysics and oil exploration. As it stands, there is a challenge in understanding the connection between the times measured in Free Induction Decay Nuclear Magnetic Resonance experiments and the shape of samples. In this work, suspensions and watersaturated densely-packed porous media with the volume fraction of the glass solid phase in the range from 10–4 to ∼1 are found to exhibit FID decay rates proportional to the square root of the volume fraction of the solid phase of the samples. A model of spheres in liquid is proposed for the description of such behavior.